Relationship between employment values and college students’ choice intention of slow employment: A moderated mediation model - Wang, Ting; Li, Shiqing (Frontiers in Psychology, 2022)
This study examined the impact of employment values on college students’ choice intention of slow employment, as well as the role of employment anxiety and social support in this process. A questionnaire survey was conducted among students from several universities in Haidian and Changping Districts of Beijing to test a theoretical model. It was found that the employment long-term income orientation and employment cost avoidance orientation significantly positively predicted the choice intention of slow employment, and employment anxiety played a mediating role in this relationship. The short-term income orientation of employment significantly negatively affected the choice intention of slow employment. Social support moderated the impact of the long-term and short-term employment income orientation on employment anxiety and the mediation effect of employment anxiety. This study contributes to the literature on college students’ employment psychology and behavior, and it provides an approach for colleges and universities, society at large, families, and college students to reduce the choice intention of slow employment and achieve fuller employment.